2017
DOI: 10.3390/nu9111180
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Endogenous Sphingolipid Metabolism in Chronic Inflammation

Abstract: Chronic inflammation is a common underlying factor in many major metabolic diseases afflicting Western societies. Sphingolipid metabolism is pivotal in the regulation of inflammatory signaling pathways. The regulation of sphingolipid metabolism is in turn influenced by inflammatory pathways. In this review, we provide an overview of sphingolipid metabolism in mammalian cells, including a description of sphingolipid structure, biosynthesis, turnover, and role in inflammatory signaling. Sphingolipid metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 191 publications
2
80
0
Order By: Relevance
“…Sphingomyelin (or ceramide phosphocholine) is an amphipathic sphingolipid in which a phosphorylcholine head group is linked to ceramide [15]. In glucosylceramide (GluCer), the 1-position of ceramide is linked to a glucose residue, whereas in lactosylceramide (LacCer), it is linked to lactose [8,16].…”
Section: Classes Of Polar Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingomyelin (or ceramide phosphocholine) is an amphipathic sphingolipid in which a phosphorylcholine head group is linked to ceramide [15]. In glucosylceramide (GluCer), the 1-position of ceramide is linked to a glucose residue, whereas in lactosylceramide (LacCer), it is linked to lactose [8,16].…”
Section: Classes Of Polar Lipidsmentioning
confidence: 99%
“…SM content encompasses approximately 25% of total milk polar lipids, and SM is found at~3:1 ratio to cholesterol by mass [6]. While health effects of PLs from eggs [7] and SLs [8] have been reviewed previously, the health effects of consuming milk polar lipids have not been reviewed extensively. Since the SLs found within MFGM are known to impact various aspects of lipid metabolism [9,10], gut microbiota [10], and inflammation [9,11], milk polar lipids may be considered as food matrix factors that may confer health benefits and/or impact effects of other dietary lipids, with implications for full-fat vs. lower-fat dairy varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Also, dietary choline intake has been associated with lower inflammation markers such as CRP, 268 interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) in a cross sectional study 269 23 involving healthy participants [46]. Pre-clinical studies showed potential anti-inflammatory 270 effects of sphingolipids (with SM as main contributor) but the limited number of human studies 271 and the use of complex phospholipid mixtures instead of single phospholipids, make it difficult 272 to conclude on the effects of sphingolipids on inflammation [47]. In the present study, we did 273 not observe any association between dietary choline and CRP.…”
mentioning
confidence: 99%
“…These findings suggest that dietary SM may work via effects on gut microbiota, which is supported by a recent mouse study showing dietary SM altered gut microbiota in high fat diet-fed mice [ 84 ]. More research is warranted to better understand the effects of dietary SM on chronic disease progression, including determining whether such effects are solely dependent on inhibiting lipid absorption or due to other reported effects on gut microbiota and inflammation [ 85 ].…”
Section: Dietary Cholesterol From Egg Intake and Lipoprotein Metabmentioning
confidence: 99%